Mdm2 Promotes Odontoblast-like Differentiation by Ubiquitinating Dlx3 and p53. (March 2020) - Zheng, H.; Yang, G.; Fu, J.; Chen, Z.; Yuan, G.
Dentin is an important structural component of the tooth. Odontoblast differentiation is an essential biological process that guarantees normal dentin formation, which is precisely regulated by various proteins. Murine double minute 2 (Mdm2) is an E3 ubiquitin ligase, and it plays a pivotal role in the differentiation of different cell types, such as osteoblasts and myoblasts. However, whether Mdm2 plays a role in odontoblast differentiation remains unknown. Here, we investigated the spatiotemporal expression of Mdm2 by immunostaining and found that Mdm2 was highly expressed in the odontoblasts and slightly in the dental papilla cells of mouse incisors and molars. Gene knockdown and overexpression experiments verified that Mdm2 promoted the odontoblast-like differentiation of mouse dental papilla cells (mDPCs). Intranuclear colocalization and physical interaction between Mdm2 and distal-less 3 (Dlx3), a transcription factor important for odontoblast differentiation, was found during the odontoblast-like differentiation of mDPCs by double immunofluorescence and immunoprecipitation. Mdm2 was proved to monoubiquitinate Dlx3, which enhanced the expression of Dlx3 target gene Dspp . In addition, p53, the canonical substrate of Mdm2, was validated to be also ubiquitinated but degraded by Mdm2 during the odontoblast-like differentiation of mDPCs. Gene knockdown experiments confirmed that p53 inhibited the odontoblast-like differentiation of mDPCs. p53 and Mdm2 double knockdown partially rescued the reduced odontoblast-like differentiation by knockdown of Mdm2 alone. Taken together, our study revealed that Mdm2 promoted the odontoblast-like differentiation of mDPCs by ubiquitinating both Dlx3 and p53. On one hand, the monoubiquitination of Dlx3 by Mdm2 led to upregulation of Dspp, which is a marker of the odontoblast differentiation. On the other hand, ubiquitination of p53 by Mdm2 resulted in its degradation, which eliminated the inhibitory effect of p53 on the odontoblast-like differentiation of mDPCs.